A glimpse on the function of chitosan as a dental hemostatic agent - Lestari, Widya; Wan Yusry, Wan Nur Aisyah; Haris @ Harith, Muhammad Salahuddin; Jaswir, Irwandi; Idrus, Erik (Elsevier, 2020)
Managing a bleeding patient can be a challenge during dental surgery. Profuse hemorrhage due to platelet defects, coagulation disorders, vascular anomalies, medication-induced patients, as well as inherited bleeding ailments result in soft tissue hematoma, septic shock, compromised airway, and in some severe cases, death could occur. Avast array of surgical hemostatic agents are available to stop bleeding, including chitosan-based hemostatic agents. Chitosan has an advantage over other topical hemostatic materials for its ability to promote shorter bleeding times and assist in healing. Massive behind-the-scene research and development efforts are ongoing to increase the performance of chitosan as a hemostatic agent. Numerous studies on chitosan use in dental hemostasis have registered it as being safe, biodegradable, biocompatible, promoting healing, antimicrobial and bioactive. This article reviews the application of chitosan in managing hemostasis in dental patients.